Social and Pedagogical Actualities of Training of Future Physical Training Teachers for Organizing Individual Work with Pupils - Alieksieiev, Oleksandr (Pedagogical Discourse, 2021)
The article theoretically analyses the essence of the problem of social and pedagogical actualities of training of future physical training teachers for organizing individual work with pupils. It has been emphasized that improving and modernization of physical education in secondary school takes into account traditional approaches to physical education of the younger generation. It has been found that nowadays, in physical education and sports education there is a reorientation of the target settings of learning to achieve the norms of physical fitness that correspond to the age of pupils, as a result of increasing the quality of personal development of each pupil. There is a borrowing of new concepts by teachers of physical training, advanced pedagogical experience, taking into account the requirements of the state, outlined in the legislative documents. The results of comparative analysis of scientific sources of modern scholars, where various aspects of vocational training of future physical training teachers are revealed, have been presented. General tendencies and approaches, features and contradictions have been found; social and pedagogical actualities of vocational training of future physical training teachers for organizing individual work with pupils have been concretized. It has been generalized that changes in sociocultural situation and content of pedagogical education determine the directions of improvement, functioning and development of future qualified teacher of physical training. Observation of the work of practicing physical training teachers allowed us to conclude that the actualization in public opinion of the idea of developing a culture of healthy and safe lifestyle of pupils as a strategic resource of individual and social development directs the educational community to find ways to improve physical education of schoolchildren. There is a suggestion that the conditions and factors for optimizing the vocational training of students who receive higher education in the field of educational activities in the specialties 014.11 Secondary education (Physical Training) and 017 Physical Training and Sports; build promising trajectories of the forecast of achievement of the outlined targets.